Restaurant Atmosphere and Service: Determinants of Consumer Intention to Purchase - Wendy Wendy; Wulanmeiaya Wowor; Johannes Kurniawan (International Journal Labs, 2025)
This study explores how restaurant atmosphere and service quality affect customer purchase intention in the casual dining sector, focusing on Megumi Mazesoba Restaurant. With increasing competition in the food and beverage industry, understanding the influence of environmental and service factors on consumer behavior is vital for business sustainability. The research addresses the decline in visitor numbers and revenue at Megumi Mazesoba in 2024 by assessing both the individual and combined effects of restaurant atmosphere and service quality on purchase intention. A quantitative approach was used, collecting data from 100 customers through structured questionnaires and analyzing the results with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that both restaurant atmosphere (path coefficient = 0.819) and service quality (path coefficient = 0.878) significantly and positively influence purchase intention, with service quality having a slightly stronger effect. These results highlight the importance of creating an appealing ambiance and maintaining high service standards to enhance customer satisfaction and loyalty. From a business management perspective, the study suggests that restaurant managers should focus on cleanliness, staff training, and aesthetic improvements to foster positive customer experiences and encourage repeat visits.